PENGARUH PEMBELAJARAN MANDIRI BERBASIS LITERASI DIGITAL DAN KEGIATAN TERSTRUKTUR TERHADAP KEMAMPUAN KEMANDIRIAN MAHASISWA DI IAIN CURUP - Amrullah Amrullah (Yayasan Literasi Kita Indonesia, 2022)
The aim of this research is to find out the influence of independent learning models based on digital literacy and structured assignments on the independence abilities of students of the Islamic Education Study Program (PAI) Institut Agama Islam Negeri (IAIN) Curup. This research used a non-experimental research design. The sampling technique used is total sampling by taking the entire population to be used as research respondents. The samples in this study were students of the PAI Study Program, IAIN Curup class 5C and 5D in the 5th Semester who took the subject of Islamic Education Philosophy for the Academic Year 2021- 2022. Based on statistical analysis of this study, it was used to determine the relationship between independent learning models based on digital literacy and students' independence ability, showing tcount of 8,530 which was greater than ttable of 2,056, then to determine the relationship between structured assignments and independence ability, tcount of 35,467 was greater than ttable of 2.056, the results of the analysis also show that the Fcount is 571.6 greater than Ftable 3.34, so it can be concluded that there is the influence of independent learning models based on digital literacy, either partially or simultaneously, on the independence ability of students of the Islamic Education Study Program (PAI) Institut Agama Islam Negeri (IAIN) Curup